2009
DOI: 10.1074/jbc.m109.032433
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like Receptors of the Ascidian Ciona intestinalis

Abstract: Key transmembrane proteins in the innate immune system, Toll-like receptors (TLRs), have been suggested to occur in the genome of non-mammalian organisms including invertebrates. However, authentic invertebrate TLRs have been neither structurally nor functionally investigated. In this paper, we originally present the structures, localization, ligand recognition, activities, and inflammatory cytokine production of all TLRs of the ascidian Ciona intestinalis, designated as Ci-TLR1 and Ci-TLR2. The amino acid seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 43 publications
2
58
1
Order By: Relevance
“…The lack of PAMPs recognition was consistent with previous reports for amphioxus and Drosophila [6,29]. In contrast, Sasaki et al demonstrated that ascidian Cionaintestinalis TLRs show low level responses to high concentrations of PAMPs [30], however, such a response is too weak to distinguish from C. intestinalis TLR's authentic ability and the background response of cell line. However, these evidences suggest that specific PAMP recognition of TLR might appear during evolution of vertebrates.…”
Section: Discussionsupporting
confidence: 90%
“…The lack of PAMPs recognition was consistent with previous reports for amphioxus and Drosophila [6,29]. In contrast, Sasaki et al demonstrated that ascidian Cionaintestinalis TLRs show low level responses to high concentrations of PAMPs [30], however, such a response is too weak to distinguish from C. intestinalis TLR's authentic ability and the background response of cell line. However, these evidences suggest that specific PAMP recognition of TLR might appear during evolution of vertebrates.…”
Section: Discussionsupporting
confidence: 90%
“…At a minimum, Ciona could represent the basic functional requirements for homeostasis in the gut of chordates. Ciona possesses a competent innate immune system (Azumi et al, 2003; Shida et al, 2003) and includes AMPs (Di Bella et al, 2011; Fedders and Leippe, 2008), two TLRs with multi-ligand binding potential (Sasaki et al, 2009), GNBPs, lipopolysaccharide binding protein (LBP), a variety of C-type lectins and other PRRs, tumor necrosis factor (TNF) (Azumi et al, 2003), mannose binding lectin (MBL) (Skjoedt et al, 2010), complement protein C3 (Marino et al, 2002), as well as the variable region-containing chitin-binding proteins (VCBPs), a relatively small family of immunoglobulin domain-containing proteins (Dishaw et al, 2011). …”
Section: Tunicates: Representatives Of the Early Chordate Gutmentioning
confidence: 99%
“…Like most other animals, Ciona likely uses AMPs as a first line of defense (Di Bella et al, 2011; Fedders and Leippe, 2008; Lu et al, 2014); however, response to specific bacterial products also can be viewed as being consistent with the patterns of expression of TLRs and other PRRs in gut tissues, resulting in the induction of pro-inflammatory molecules, e.g., TNF (Sasaki et al, 2009). Although the Ciona genome encodes only two TLRs, both are expressed, along with VCBPs, in distinct locations along the gut.…”
Section: Tunicates: Representatives Of the Early Chordate Gutmentioning
confidence: 99%
See 2 more Smart Citations